Paritaprevir, ritonavir, ombitasvir, and dasabuvir treatment in renal transplant patients with hepatitis C virus infection - Danış, Nilay; Toz, Hüseyin; Ünal, Nalan; Yılmaz, Mümtaz; Turan, İlker and Günşar, Fulya and Karasu, Zeki and Ersöz, Galip and Özkahya, Mehmet and Akarca, Ulus Salih (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The Social Security System of our country reimburses only paritaprevir, ritonavir, ombitasvir, and dasabuvir (PrOD) regime in treatment-naive patients with hepatitis C regardless of kidney disease. Most of our renal transplant (RT) recipients were treated with PrOD. The aim of the present study was to investigate the efficacy and safety of PrOD in RT patients with hepatitis C virus (HCV) infection in a single center real-life experience. Materials and Methods: RT recipients with a post-transplant follow-up of at least 1 year were included in the study. The patients were treated and monitored according to the guidelines. Blood levels of immunosuppressive patients were closely followed up and adjusted. Results: A total of 21 (12 male and nine female) patients were assessed. The age of the patients was 50.8±8.5 years. Ten patients were infected with G1a, 10 patients with G1b, and one patient with G4 HCV. Two patients had compensated cirrhosis. Eighteen patients were treatment-naive, and three were peginterferon+ribavirin-experienced. Sustained virologic response (SVR12) was achieved in all patients. None of the patients discontinued the treatment. Cyclosporine (Csa) and tacrolimus (Tac) doses were reduced to once a day to once a week to maintain the blood level within normal range. The most common adverse effect was anemia in patients receiving ribavirin. Renal functions did not change during the treatment period. Conclusion: In this real-life experience, all of the 21 PrOD-treated RT recipients reached SVR12. Tac or Csa serum levels were maintained within the normal range with close monitoring. PrOD regime can be successfully and safely used in RT recipients with HCV infection with close follow-up.